(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This thesis explores the distinctive characteristics of teacher training in the field of primary education. It examines the unique pedagogical, psychological, and methodological aspects that differentiate primary education teacher preparation from other levels of teacher education. The study analyzes the competencies required for primary school teachers, the structure of training programs, the role of practice-oriented learning, and the challenges faced by higher education institutions in preparing qualified primary education specialists. Special attention is given to the context of non-state higher education institutions and the evolving demands of modern primary education.